If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -6 = 6(x + 6) Reorder the terms: -6 + y = 6(x + 6) Reorder the terms: -6 + y = 6(6 + x) -6 + y = (6 * 6 + x * 6) -6 + y = (36 + 6x) Solving -6 + y = 36 + 6x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + y = 36 + 6 + 6x Combine like terms: -6 + 6 = 0 0 + y = 36 + 6 + 6x y = 36 + 6 + 6x Combine like terms: 36 + 6 = 42 y = 42 + 6x Simplifying y = 42 + 6x
| 7xc=-3 | | 8x-1+15x+3x+9=360 | | Z+5=5 | | 5x+7(-x-14)=-88 | | 13x-30=9 | | 10x+3+3x+24=180 | | 24x^2+-12x+-12=0 | | 22/25-7/10 | | 5/20=30/x | | 8x-1+15x+3x+9=90 | | y+4=4(x+7) | | -7y-7=-5(y+5) | | Log(4x+12)=2 | | 72x+56=-84-37x | | 3u-5=10 | | 5/20=3-/x | | 8x-1+15x+3x+9=180 | | 8x-6y=56 | | Q/6--112=125 | | 0=-16x^2+560 | | -9/p-3=3/5 | | 12=-7v+5(v+6) | | y+7=4(x-9) | | 20+-6n=-12+-2n | | 2w+30=460 | | cos(0.5)x=-1 | | 1/3x^2-10=18 | | -3x+2(4x-9)=-53 | | 7y-6=13y+6 | | 6x+3x=12y+11 | | 2r^2-8r-42=0 | | 1/31/3x^2-10=18 |